Sistema de Gestión para el control de la Producción y Propaganda de la empresa Borojo Amazónico Borama Cia. Ltda. - Llumiquinga Guamán, Myriam Teresa (2013)
Actuality don´t exist standard in order to process control in the enterprise, this has been controlled based in specific characteristic. In the Borojo Amazonico Borama Cia Ltda., the developer and propaganda process generated a big information volume, this information was processing manually, make difficult analyze and obtain know for decision taken. Defined who general objective developed one system for controlling the productive and propaganda process in the Borojo Amazónico Borama Cia Ttda enterprise.